(untitled) (Latakia University Journal -Biological Sciences Series, 2017)
تعد زراعة النباتات الطبية والعطرية بشكل عام ، ونبات إكليل الجبل بشكل خاص ، من الزراعات الاقتصادية البديلة التي انتشرت زراعتها حديثاً في سورية نظراً لملائمة الظروف الطبيعية والبيئية لزراعتها ، إضافة للمردود الاقتصادي الجيد الناتج عنها . لذلك أصبح الاهتمام بتشجيع وتطوير زراعة هذه النباتات من أهم الأهداف المحددة لإستراتيجية التنمية الزراعية المستقبلية في سورية . وقد هدف هذا البحث إلى تحقيق الأهداف التالية : 1. تحليل التكاليف الإنتاجية لإنتاج نبات إكليل الجبل في محافظة اللاذقية . 2. التقويم الاقتصادي لإنتاج نبات إكليل الجبل في محافظة اللاذقية . ونتيجة الدراسة تبين أن اهم النتائج التي توصل إليها البحث ، هي : 1. بلغ صافي الربح السنوي المحقق في الدونم الواحد المزروع بنبات إكليل الجبل في محافظة اللاذقية 200799.48 ل . س . 2. بلغ صافي الدخل المزرعي في الدونم الواحد المزروع بنبات إكليل الجبل في محافظة اللاذقية 206901.84 ل . س . 3. بلغت الكفاءة الاقتصادية الإجمالية لإنتاج نبات إكليل الجبل في محافظة اللاذقية 3.02 . Husbandry of the medicinal and aromatic plants in general and “Rosemary” in particular is considered of the alternative economical husbandry that flourished recently in Syria due to the availability of the natural and environmental conditions thereto; in addition to the good economical yield thereof. Interest, encouragement, development, and expansion of such husbandry are considered of the most important targets set for the future strategy of agricultural development in Syria. This Research has targeted to the realization of the following purposes : 1- Analysis of the costs of Rosemary production in Lattakia Governorate. 2- The economical evaluation for Rosemary production in Lattakia Governorate. The research concluded to the following: 1) The achieved annual net profit of one dunum planted with Rosemary in Lattakia Governorate has amounted to SYP /200799.48/. 2) The farming revenue of one dunum planted with Rosemary in Lattakia Governorate has amounted to SYP /206901.84/. 3) The total Economical Feasibility from Rosemary husbandry in Lattakia Governorate has amounted to 3,02